(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The best thing that parents can do for their daughters is to encourage them to take part in extracurricular activities like “Physical Fitness” classes and team sports. This will help their daughters in the long run. Over the course of the past several decades, “Physical Fitness” (P.F.) has steadily become more of a priority, especially in educational institutions such as high schools and universities.